African proverbial sayings: a paremilogical reading of Achebe's arrow of God (2012)
Africans are a culturally deep and psychologically peculiar people. Proverbs constitute a major form of collective consciousness through which Africans communicate ideas and opinions. Several studies reveal that thought patterns, attitudes and psyche of peoples are comprehensible through paremiology, the study of proverbs. Nigeria's Chinua Achebe has carved out a niche for himself as an African Proverbialist. This article examines the psycho-cultural value of proverbial sayings in his work. The application of this linguistic form as a dominant tool in the narrative technique and in the portraiture of the themes and characters is the focus of this study which takes as reference, Arrow of God, a work that concretizes the African psycho- cultural crisis. It examines the psychological, philosophical and cultural values embedded in the African proverbial folio.